Decolonizing Malay-Islamic Epistemology: Revitalizing the Intellectual Tradition in the Nusantara through a Philosophy of Science Perspective - Candra Darmawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The Malay-Islamic scholarly tradition once served as a crucial foundation for the development of knowledge in the Nusantara through the harmonious integration of revelation, reason, and lived experience. However, colonialism has constructed a hierarchy of knowledge that positions Western epistemology as the center of rationality, while reducing the Malay-Islamic intellectual heritage to non-scientific local knowledge. This article aims to dismantle the structures of coloniality of knowledge that continue to be reproduced through modern education systems in the Malay–Islamic world and to offer the Transformative Islam framework as a more emancipatory epistemic alternative. Employing an interpretive textual analysis grounded in decolonial theory and the Islamic philosophy of science, this study traces epistemic subordination in the history of education, revitalizes the Malay–Islamic intellectual genealogy, and formulates a postcolonial pedagogical praxis to build the scientific autonomy of Malay Muslims. The findings show that colonial epistemological models have produced a disconnection from manuscripts, language, and the core values of adab, tawḥīd, and ḥikmah within Malay-Islamic epistemology. These findings are translated into a postcolonial pedagogical praxis with direct implications for contemporary education, including curriculum redesign, integrative teaching approaches that bridge religious and scientific knowledge, and community-engaged research to strengthen scientific agency. The article argues that such educational transformation is essential for restoring epistemic sovereignty and revitalizing Malay Islam as a knowledge civilization in the modern era.